Curriculum Regulation Document Analysis on Strengthening Character Values through Physical Education - Zainal Widyanto; Lestari Wulandari S (Universitas Negeri Semarang, 2024)
Character education has become a fundamental aspect of the national curriculum, aiming to develop students' moral integrity, responsibility, discipline, and cooperation. Physical education (PE), with its emphasis on physical activity, teamwork, and sportsmanship, serves as a strategic medium to internalize these character values. This study analyzes curriculum regulation documents to examine how character values are integrated into physical education in Indonesian schools. The research object consists of national curriculum policy documents, including the 2013 Curriculum, the Merdeka Curriculum, the Regulation of the Minister of Education and Culture No. 22 of 2016, and the official guidelines for Physical Education learning. The primary objective of this study is to explore the extent to which these documents reflect a commitment to character development through PE. A qualitative research method with a document analysis approach was employed. Data were analyzed using content analysis techniques, focusing on the identification of explicit and implicit character values embedded within the learning objectives, core competencies, and learning outcomes related to PE. The findings indicate that curriculum regulations provide substantial normative support for character education, particularly in promoting values such as discipline, respect, honesty, cooperation, and responsibility. However, the degree of clarity and operational guidance in implementing these values varies across different documents. In conclusion, while regulatory documents recognize the importance of character development through physical education, there remains a gap between policy articulation and practical implementation. This study highlights the need for clearer pedagogical guidelines to optimize PE as a vehicle for character education in Indonesian schools.